Amorphous Silicon-Germanium Films with Embedded Nanocrystals for Thermal Detectors with Very High Sensitivity. (17th February 2016) - Calleja, Cesar; Torres, Alfonso; Rosales-Quintero, Pedro; Moreno, Mario
Abstract : We have optimized the deposition conditions of amorphous silicon-germanium films with embedded nanocrystals in a plasma enhanced chemical vapor deposition (PECVD) reactor, working at a standard frequency of 13.56 MHz. The objective was to produce films with very large Temperature Coefficient of Resistance (TCR), which is a signature of the sensitivity in thermal detectors (microbolometers). Morphological, electrical, and optical characterization were performed in the films, and we found optimal conditions for obtaining films with very high values of thermal coefficient of resistance (TCR = 7.9% K −1 ). Our results show that amorphous silicon-germanium films with embedded nanocrystals can be used as thermosensitive films in high performance infrared focal plane arrays (IRFPAs) used in commercial thermal cameras.